2020
DOI: 10.3390/ma13214907
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cooking Oil on the Mitigation of Autogenous Shrinkage of Alkali-Activated Slag Concrete

Abstract: This paper reports an investigation into the autogenous shrinkage, mechanical, and durability performances of alkali-activated slag concrete (AASC) with emulsified cooking oil (ECO). Properties of AASC including flowability, setting time, compressive strength, autogenous shrinkage, and carbonation depth are tested to clarify the effects of the ECO. Commercially available expansion agent (EA) and shrinkage reducing agent (SRA) are also applied on AASC to compare with ECO. Experimental results show that the util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Superabsorbent polymers, lightweight aggregates, and zeolites can all provide internal curing after pre-absorption [95][96][97]. Other admixtures that can alter the reaction kinetics and microstructure of AAMs can also modify their shrinkage behaviors, but the development of strength can be compromised if the reaction is delayed [47,98].…”
Section: Shrinkagementioning
confidence: 99%
“…Superabsorbent polymers, lightweight aggregates, and zeolites can all provide internal curing after pre-absorption [95][96][97]. Other admixtures that can alter the reaction kinetics and microstructure of AAMs can also modify their shrinkage behaviors, but the development of strength can be compromised if the reaction is delayed [47,98].…”
Section: Shrinkagementioning
confidence: 99%
“…In this study, a data bank was first built by conducting a literature review to collect extensive and detailed information on the mix proportions, physical properties of composites, and mechanical properties of AASC. In total, 181 sets of AASC design mix produced with different mix proportions were gathered from different reliable sources consisting of previously published or available studies on the behaviour of AASC [30,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. As the data obtained for this study were mainly from various sources, the developed ANN-based prediction model would be more general.…”
Section: Data Bank Constructionmentioning
confidence: 99%
“…Rath et al [17] investigated the effect of organic rubber latex on the pore structure and capillary suction of geopolymer concrete and found that the addition of organic rubber latex can effectively decrease the early-age shrinkage of geopolymers. Huang et al [18] reported that the use of edible oil can reduce the surface tension of concrete and make its internal structure denser, thereby effectively reducing the autogenous shrinkage of concrete by 68% without obvious strength loss. In addition, different from other frequently-used measurements for mitigating the shrinkage by adding internal curing admixtures [19][20] or shrinkage-reducing admixtures [11,[21][22], modifying the wettability through organic admixtures can also enable the geopolymer with water repellence and corrosion resistance performance [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%